The effects of the Er:YAG laser on trabecular bone micro-architecture: Comparison with conventional dental drilling by micro-computed tomographic and histological techniques [version 1; referees: 2 approved] - Jihad Zeitouni; Bret Clough; Suzanne Zeitouni; Mohammed Saleem; Kenan Al Aisami; Carl Gregory (F1000Research, 2017)
Background: The use of lasers has become increasingly common in the field of medicine and dentistry, and there is a growing need for a deeper understanding of the procedure and its effects on tissue. The aim of this study was to compare the erbium-doped yttrium aluminium garnet (Er:YAG) laser and conventional drilling techniques, by observing the effects on trabecular bone microarchitecture and the extent of thermal and mechanical damage. Methods: Ovine femoral heads were employed to mimic maxillofacial trabecular bone, and cylindrical osteotomies were generated to mimic implant bed preparation. Various laser parameters were tested, as well as a conventional dental drilling technique. The specimens were then subjected to micro-computed tomographic (μCT) histomorphometic analysis and histology. Results: Herein, we demonstrate that mCT measurements of trabecular porosity provide quantitative evidence that laser-mediated cutting preserves the trabecular architecture and reduces thermal and mechanical damage at the margins of the cut. We confirmed these observations with histological studies. In contrast with laser-mediated cutting, conventional drilling resulted in trabecular collapse, reduction of porosity at the margin of the cut and histological signs of thermal damage. Conclusions: This study has demonstrated, for the first time, that mCT and quantification of porosity at the margin of the cut provides a quantitative insight into damage caused by bone cutting techniques. We further show that with laser-mediated cutting, the marrow remains exposed to the margins of the cut, facilitating cellular infiltration and likely accelerating healing. However, with drilling, trabecular collapse and thermal damage is likely to delay healing by restricting the passage of cells to the site of injury and causing localized cell death.